“Do I Care that You Are Credible and We Are Similar?” Examining Credibility and Similarity as Experienced by Social Media Followers - Tan, Caroline S. L. (Communication Today, 2021)
This study explores the roles that similarity and credibility play in the influencer-follower relationship as experienced by followers. The data was collected using face-to-face semi-structured interviews that were conducted with 37 young adults, analysed using thematic analysis. The findings show that there were shifts in how followers translated similarity and credibility, transforming the motives behind following influencers. Followers also do not view themselves as having similar values or personality traits to influencers. The level of trust and perceived credibility were lower versus that of existing literature. The study also shows that similarity plays a part in the decision to unfollow. The findings reflect changes in follower behaviour and ultimately the way they consume content from influencers.